Divulguação nas redes sociais digitais e a influência na decisão de compra dos consumidores de suplementos alimentares - Holanda, Juan Lucas Ferreira de (Universidade Federal Rural do Semi-Árido, 2018)
Living in a digital era, where the internet allows a wide dissemination of information, social networks promote a significant volume of inf ormation, relationships, opinions, consumption of products and services, etc. This interaction between users causes companies to advertise their brands, show themselves more, and relate to their audience within that virtual environment. In this perspective, this study aims to analyze whether the disclosures of Mossoro’s companies in the food supplements sector in digital social networks influence the decision to buy of the consumers. For that, the methodology used was qualitative. The researched universe was the public that practices physical activity and consumes food supplements, having as a sample 150 respondents. The data collection instrument was a questionnaire with eight closed questions and one opened, applied in four academies, in order to know if the postings in digital social networks influence the purchase decision. The results showed that ninety-seven percent of the respondents consider that the publications influence when deciding to buy some food supplement.
Monografia
Keywords: Divulgação; Redes Sociais; Decisão de compra; Suplementos Alimentares; Disclosure; Social networks; Buying decision; Food supplements; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO